Overall architecture design of row/column scanning silicon-based focal plane switch array LiDAR transmitter system - Yu Wang; Yue Wang; Zeyang Zhang; Hang Cheng; Yuanhui Li; Guohui Yang; Kuang Zhang; Chunhui Wang (APL Photonics)
The focal plane switch array (FPSA) is one of the most promising solutions for optical detection and ranging—light detection and ranging (LiDAR)—due to its ease of control and lack of sidelobes. However, as the emitted field of view continues to increase, its scalability and system integration face significant challenges. To address this issue, we propose and fabricate a novel row/column scanning FPSA LiDAR transmitter system architecture. This architecture allows each optical path to control multiple grating couplers for simultaneous transmission, integrating both time-domain and spatial detection to enhance system detection efficiency and accuracy. For an N × N transmitter array, the number of required optical switches is reduced to 1/N of that needed in existing FPSA architectures, significantly decreasing the complexity of modulation and integration. Furthermore, to improve the performance of two-dimensional beam scanning, we utilized topological optimization and deep learning techniques to customize the design and optimization of key components. The functionality and low complexity of the designed architecture were validated through the simulation of a 64 × 64 transmitter array. By fabricating and testing a 4 × 4 transmitter array, we confirmed the feasibility of the designed architecture. The test results indicate that, benefiting from the meticulous optimization of each component, the scanning angle of the emitted beam reached 4° × 4°, the beam divergence angle achieved 0.05° × 0.05°, and the FWHM reached 0.13 μm, with the extinction ratio of each channel exceeding 23 dB.